2007
DOI: 10.1590/1809-9823.2007.10023
|View full text |Cite
|
Sign up to set email alerts
|

Os Efeitos de um Programa de Fisioterapia como Promotor de Saúde na Capacidade Funcional de Mulheres Idosas Institucionalizadas

Abstract: Resumo Com o aumento da população idosa mundial, tornou-se preocupação de várias áreas do conhecimento identificar as condições que permitem envelhecer com qualidade. A instituição asilar se torna um tema relevante, pois se observa uma demanda aumentada por instituições de longa permanência. A preservação e a manutenção da capacidade funcional são objetivos prioritários na saúde do idoso. Objetivo analisar os efeitos de um Programa de Fisioterapia como promotor de saúde na capacidade funcional e identificar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
12

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
(14 reference statements)
0
4
0
12
Order By: Relevance
“…36 Health promotion has developed as a response to this challenge of achieving old age without disability, encompassing actions directed at strengthening the physical and mental abilities of individuals, as well as actions directed at changes in social, environmental and economic conditions, in order to lessen their impact on public and individual health. 37 Hence the importance of the participation of older people in health promotion programs that focus on prevention of disabilities as a priority.…”
Section: Discussionmentioning
confidence: 99%
“…36 Health promotion has developed as a response to this challenge of achieving old age without disability, encompassing actions directed at strengthening the physical and mental abilities of individuals, as well as actions directed at changes in social, environmental and economic conditions, in order to lessen their impact on public and individual health. 37 Hence the importance of the participation of older people in health promotion programs that focus on prevention of disabilities as a priority.…”
Section: Discussionmentioning
confidence: 99%
“…20 In our study, the elderly showed independence in their activities even with high blood pressure and other diseases such as diabetes and arthrosis. However, in the study by Montenegro 21 the worsening of some functional activities showed a correlation with the presence of associated diseases and the advanced age of the patient.…”
Section: Resultsmentioning
confidence: 85%
“…Dentro deste contexto, a presença do profissional fisioterapeuta é de grande importância nas ILPI's pois os idosos que nelas residem possuem muitas vezes, várias doenças associadas que os tornam mais vulneráveis às quedas 10 e a fisioterapia nas ILPI's tem como principal objetivo a preservação ou a recuperação da capacidade funcional do idoso, mantendo a independência funcional e um bom nível de atividade física o máximo de tempo possível 10,11 .…”
Section: Introductionunclassified